Hospitalization and mortality rates of malignant prostatic neoplasms in Brazil: A cross-sectional study from 2008 to 2018 - Alberto Fernando Oliveira Justo; Rita de Cássia Collaço; Anna Ligia Oenning Soares; Caroline Marques Caloi; Camila Stefani Estancial; Guilherme Lemos; Fabio Henrique da Silva; Eduardo Costa Alexandre; Fabiano Beraldi Calmasini (Universidade de São Paulo, 2024)
Abstract Prostate cancer (PCa) is a highly prevalent condition among men worldwide, resulting in reduced quality of life and increased costs to health systems due to hospitalization and death. This study aimed to explore and understand the evolution of PCa in Brazil from 2008 to 2018. Data were obtained from the National Health System Department of Informatics (DATASUS) using code C61 for malignant prostatic neoplasms. We presented the hospitalization and mortality rates in a temporal-, regional- and age-dependent manner. From 2008 to 2018, a year-dependent increase in hospital admissions due to PCa was reported in Brazil, in which the Southeast region showed the highest prevalence. Men aged ≥80 and those 70-79 years old had similar hospitalization rates, followed by men aged 60-69, 50-59, 40-49 and 30-39 years old. Similarly, an increase in deaths due to PCa was reported during this period, with the highest rates seen in the Southeast. Men aged ≥80 years had higher mortality rates, followed by those aged 70-79, 60-69, 50-59, 40-49 and 30-39 years old. The results obtained indicate an age- and region-dependent increase in PCa morbidity and mortality in Brazil overtime and may contribute to the ongoing discussion on the role and future perspective of the health care system in Brazil.